Peran Kepemimpinan Transformasional Kepala Sekolah dan Iklim Sekolahh Yang Kondusif Terhadap Kinerja Guru di Sekolah Terpadu Bina Bangsa Serang - Islahiyah Islahiyah; Ramdan Ramdan; Atikah Atikah; Mutoharoh Mutoharoh (Journal of Innovative and Creativity, 2025)
This study aims to determine transformational leadership role of the principal and a conducive school climate on teacher performance at the Bina Bangsa Serang Integrated Islamic School. In the 21st century, demands on the world of education are increasing, therefore teacher performance is an important component in achieving educational goals. Transformational leadership is characterized by the leader's ability to inspire, motivate, and empower subordinates. Meanwhile, a conducive school climate creates a supportive, fair, and collaborative environment. This study uses a quantitative correlational approach with a purposive sampling technique for 80 teachers. Data were collected through online questionnaires and analyzed statistically. The population in this study was 60 teachers working at Bina Bangsa Serang Integrated Islamic School. The results showed that there was a significant positive relationship between transformational leadership and school climate with teacher performance. Effective leadership and a positive work environment have been shown to increase teacher motivation, collaboration, innovation, and effectiveness in the learning process. Partially, the transformational leadership of the principal has a positive and significant effect on teacher performance by 21.4%. The influence of the teacher's work climate on teacher performance is also positive and significant at 39%. Simultaneously, the transformational leadership of the principal and the teacher's work climate have a positive and significant influence on teacher performance.